Publishing a master's thesis: a guide for novice authors. - Resta RG; McCarthy Veach P; Charles S; Vogel K; Blase T; Palmer CGS (Journal of Genetic Counseling, 2010)
Publication of original research, clinical experiences, and critical reviews of literature are vital to the growth of the genetic counseling field, delivery of genetic counseling services, and professional development of genetic counselors. Busy clinical schedules, lack of time and funding, and training that emphasizes clinical skills over research skills may make it difficult for new genetic counselors to turn their thesis projects into publications. This paper summarizes and elaborates upon a presentation aimed at de-mystifying the publishing process given at the 2008 National Society of Genetic Counselors Annual Education Conference. Specific topics include familiarizing prospective authors, particularly genetic counseling students, with the basics of the publication process and related ethical considerations. Former students' experiences with publishing master's theses also are described in hopes of encouraging new genetic counselors to submit for publication papers based on their thesis projects.